Conceptualising risk culture on enterprise risk management (ERM) implementation in construction companies / Wong Ching Ching ... [et al.] - Wong, Ching Ching; Mohd Rahim, F.A.; Loo, Siaw Chuing; Zainon, N.; Aziz, N.M. (Faculty of Architecture, Planning and Surveying (FSPU), and UiTM Press Universiti Teknologi MARA (UiTM), Selangor, Malaysia., 2020)
In today's global economy, inadequate risk management and lack of risk culture can threaten a company’s viability. Since construction industry is subjected to uncertainty, construction Public Listed Companies (PLCs) need to implement Enterprise Risk Management (ERM) as an effective technique in managing risk holistically. Although the importance of ERM is widely accepted, the influence of risk culture in its’ implementation is unexplored. This paper presents a conceptual model that shows the relationship between risk culture and ERM implementation. The dependent variable is ERM implementation, consist of four dimensions namely risk identification and risk assessment; risk treatment; monitor and consult; communicate and consult. The independent variables, risk culture compromise of six dimensions, which are risk policy and risk appetite; key risk indicators; accountability; incentives; risk language and internal relationships. This study aims to empirically test the relationship between risk culture and ERM implementation among Malaysian construction public listed companies. Quantitative method through questionnaire survey is adopted as data collection for this study. Risk culture is expected to have direct effects and significantly influence ERM. This study contributes to enhance the body of knowledge in ERM especially in understanding significant of risk culture that influence its’ implementation from Malaysian perspective.